2019
DOI: 10.2147/jpr.s194881
|View full text |Cite
|
Sign up to set email alerts
|

<p>Real-life management of patients with breakthrough cancer pain caused by bone metastases in Spain</p>

Abstract: Purpose: We aimed to explore the characteristics, and real-life therapeutic management of patients with breakthrough cancer pain (BTcP) caused by bone metastases in Spain, and to evaluate physicians’ opinion of and satisfaction with prescribed BTcP therapy. Participants and methods: For the purposes of this study, an ad-hoc questionnaire was developed consisting of two domains: a) organizational aspects and care standards; b) clinical and treatment variables of bone metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In our analysis, a significant association ( p < 0.10) was found between the presence of bone metastases and BTcP. This finding confirms our expectations because bone secondaries represent the main cause of predictable BTcP [ 25 , 36 ]. Moreover, the analysis showed that spontaneous (or non-predictable) BTcP is also related to metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…In our analysis, a significant association ( p < 0.10) was found between the presence of bone metastases and BTcP. This finding confirms our expectations because bone secondaries represent the main cause of predictable BTcP [ 25 , 36 ]. Moreover, the analysis showed that spontaneous (or non-predictable) BTcP is also related to metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…More than 50% of patients reported unpredictable BTcP and 44.3% experienced predictable BTcP episodes. In this study, 43 a ROO was the treatment of choice for bone metastatic BTcP. In the palliative care setting, the overall percentage of sublingual fentanyl prescriptions was higher.…”
Section: Discussionmentioning
confidence: 73%
“…There is evidence that QOL is rarely included as a treatment outcome for BTcP in patients with metastases. Ferrer Albiach et al 43 enrolled 386 patients with bone metastases and BTcP in any care setting in Spain. More than 50% of patients reported unpredictable BTcP and 44.3% experienced predictable BTcP episodes.…”
Section: Discussionmentioning
confidence: 99%
“…64 Many breakthrough pain episodes of greater intensity in the advanced stages of cancer are due to bone pain caused by metastasis 17 and require additional proper therapy. Albiach et al 76 collected data from patients with metastatic bone disease and BTcP and demonstrated that primary cancer was mainly localized in the lungs and prostate (85 out of 386 patients or 22%), and BTcP occurred spontaneously and suddenly with high pain intensity in 70.6% of cases.…”
Section: Reviewmentioning
confidence: 99%